Advances in hospitality and leisure - Chen, Joseph S. (Emerald Publishing Limited, 2024)
Advances in Hospitality and Leisure (AHL), a double-blind peer view journal published annually since 2004, attempts to promote seminal and innovative research outputs pertaining to hospitality, leisure, tourism, and lifestyle. Specifically, this journal encourages researchers to investigate new research issues and problems that are critical but have been largely ignored while providing a forum that will disseminate singular thoughts advancing empirical undertakings both theoretically and methodologically. This twentieth annual volume includes nine full papers and one research note. As for data collection, the articles present both quantitative and qualitative research methods. The contributors to the present issue come from 10 nations/regions entailing Australia, Germany, Japan, South Korea, Switzerland, Thailand, Taiwan, the United States of America, Uruguay and Uzbekistan.
Includes index.
Keywords: Tourism.; elektronické knihy; electronic books